2009
DOI: 10.1007/s12264-009-6123-2
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of aging by unc-13 and sbt-1 in Caenorhabditis elegans is temperature-dependent

Abstract: Objective To investigate the role of environmental factor-temperature in the regulation of aging process by unc-13and sbt-1 in Caenorhabditis elegans. Methods The lifespan, the speed of pharynx pumping, and the intestinal autofluorescence of unc-13 and sbt-1 mutants were examined at different temperature conditions. In addition, to exclude the possible influences from other factors in unc-13 and sbt-1 mutants, the dauer formation, the thermotaxis, the brood size and the population

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Based on studies of ortholog genes in C. elegans aging models, it has been suggested that some neurexins also contribute to the process of aging [19]. Here, we investigated the NRX-1 gene, the C. elegans ortholog of the mammalian CNTNAP4 gene [20].…”
Section: Resultsmentioning
confidence: 99%
“…Based on studies of ortholog genes in C. elegans aging models, it has been suggested that some neurexins also contribute to the process of aging [19]. Here, we investigated the NRX-1 gene, the C. elegans ortholog of the mammalian CNTNAP4 gene [20].…”
Section: Resultsmentioning
confidence: 99%
“…Lifespan assay was performed basically as described [65] [66] . In the test, the hermaphrodites were transferred daily for the first 4 days of adulthood.…”
Section: Methodsmentioning
confidence: 99%
“…Lifespan assay was performed as previously described (He et al, 2009;Wang et al, 2013). Hermaphrodites were transferred daily for the first 4 days of adulthood.…”
Section: Lifespan Assaymentioning
confidence: 99%